João do Rio e a cidade do Rio de Janeiro em movimento: os andares, as lacunas, as contradições e os embates numa metrópole que se quer moderna - Antonio Edmilson Martins Rodrigues (Interseções)
This article discusses the ways of receiving João do Rio’s work in the relatoins it establishes with the city and in the way of understanding his actions as a pedestrian in the city, revealing what is behind the modernization initiated in the early years of tentieth century and thus produzing a set of studies/essas in the form of chronicles, short stories, theather and criticismo and the critical reception given to him and his work, through those who reconignized im him someone dangerous who needed to be eliminated from the history of the city of Rio de Janeiro, causing his death in 1921.